Strategic Language Alternation in K-Pop Digital Discourse: A Study of NewJeans’ Phoning Podcast - Nasyah Azalia Indria Putri; Risa Triarisanti; Ashanti Widyana (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2026)
The globalization of K-pop has increasingly positioned multilingual communication as a central feature of idol-fan interaction, yet bilingual practices in digital fan platforms remain underexplored. NewJeans’ Phoning podcast provides a rich site for observing such practices, where members alternate between Korean and English while addressing fellow members and a global fan audience. This study describes the forms of code-switching and code-mixing in the podcast and explores the communicative factors motivating these language choices. Drawing on Blom and Gumperz’s framework (Hudson, 1996), Muysken’s (2000) typology, and Bhatia and Ritchie’s (2004) motivational categories, the study employs a qualitative descriptive design. Data were collected through repeated listening, verbatim transcription, and systematic coding of bilingual tokens from a single 48-minute episode. The analysis identified 58 instances of language alternation: 14 cases of code-switching and 44 cases of code-mixing. Within code-switching, conversational shifts were most dominant (8 instances), followed by metaphorical (5) and situational (1), indicating that language alternation occurs most naturally as part of habitual bilingual interaction. Within code-mixing, insertion was the most dominant pattern (23 instances), followed by alternation (21 instances), while congruent lexicalization was entirely absent, reflecting the distinct syntactic structures of Korean and English. Motivation analysis shows that message qualification is the most recurrent factor (16 instances), followed by topic comment (13) and reiteration (8), highlighting the strategic use of bilingual resources to clarify meaning, maintain conversational flow, and engage both domestic and international audiences. Overall, the findings illustrate how K-pop idols negotiate accessibility (English) and in-group intimacy (Korean) through bilingual discourse in a digitally mediated setting. These results contribute to research on multilingualism in digital media and the role of English as a lingua franca in transnational K-pop fan communities.